Phenotypic and genotypic aspects of sorbitol-negative Escherichia coli isolated from cattle - Moawad, A; Shehawy, E; Elshayeb, T; EL-Magd, M (Journal of the Hellenic Veterinary Medical Society, 2023)
Escherichia coli especially sorbitol-negative serogroups such as O157 that produces Shiga toxin (STEC) is involved in food poisoning with severity ranging from individual cases into outbreaks that threaten human and animal health. This study aimed to evaluate phenotypic and genotypic aspects of sorbitol-negative E.coli isolated from different sources. A total of 420 samples were collected from fecal swabs and raw milk of cattle from various locations in Kafr Elsheikh government, Egypt. The prevalence of E. coli isolates was 9.3% (39/420) as was determined by bacterial culturing. The phenotype of these isolates was serologically and molecularly determined, and the results showed an overall prevalence of E. coli O157 of 23% (9/39) with a high incidence in fecal swabs samples. The multidrug resistance (MDR) phenotype as detected by antibiotic sensitivity test and confirmed by PCR revealed resistance to amoxicillin, clavulanic acid, vancomycin, ampicillin, and sulbactam with the detection of blaTEM and blaSHV MDR genes in 9 and 2 isolates, respectively. Virulence genes (stx1, stx2, eaeA) were also detected in 1, 9, 6 isolates, respectively. With these results, we could conclude that E. coli O157 was identified in not only cattle fecal swab samples but also in their milk and subsequently this could threaten animal and human health.